2004
DOI: 10.1097/01.asn.0000130858.00688.46
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Association Study Showing that Immunoglobulin A Nephropathy Is Associated with the Polymorphisms 2093C and 2180T in the 3′ Untranslated Region of the Megsin Gene

Abstract: Abstract. Immunoglobulin A nephropathy (IgAN) is considered to be a multifactorial disease with genetic and environmental factors contributing to its pathogenesis. The genes involved in susceptibility and progression of the disease have not yet been clearly elucidated. Megsin (SERPINB7) is an important candidate gene, predominantly expressed in glomerular mesangium and upregulated in IgAN. To investigate the potential role of this and other genes in IgAN, patients with biopsy-proven IgAN were recruited, as wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 23 publications
0
28
2
Order By: Relevance
“…Two studies 3,7 were performed in Caucasians, and two 9,10 in Asians. A total of 990 cases and 678 controls were included.…”
Section: Study Characteristics For 2093c/t Polymorphism With Igan Riskmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies 3,7 were performed in Caucasians, and two 9,10 in Asians. A total of 990 cases and 678 controls were included.…”
Section: Study Characteristics For 2093c/t Polymorphism With Igan Riskmentioning
confidence: 99%
“…Four studies 3,7,9,10 were identified for the analysis of the association between 2093C/T polymorphism and IgAN risk (Table 1). Two studies 3,7 were performed in Caucasians, and two 9,10 in Asians.…”
Section: Study Characteristics For 2093c/t Polymorphism With Igan Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…40 IgAN was diagnosed by renal biopsy according to the World Health Organization criteria. Systemic lupus erythematosis, Henoch-Schonlein purpura, and hepatic diseases were excluded by detailed clinical history, examination, and negative laboratory findings for hypocomplementemia, anti-DNA antibody or hepatitis B virus surface antigen.…”
Section: Study Subjectsmentioning
confidence: 99%